Practical Skills in Pre-University Education in Albania: The Challenge for an Effective and Contemporary Education - Petro, Menada; Sallata, Ilir; Senatore, Gianluca; Biryukova, Yulia Nickolaevna (Journal of Education Culture and Society, 2025)
Aim. This article aims to examine the importance of including practical skills in the pre-university curriculum and their impact on individual and social development. Pre-university education in Albania has been and continues to be mainly focused on theoretical subjects, overshadowing the acquisition of practical skills that are necessary for a pupil’s personal and professional development, especially nowadays. The article analyses the current challenges that prevent practical skills integration, such as the lack of adequate infrastructure, insufficient training of teachers about the integration of practice during the learning process and the disconnection of the educational system from the real-professional world and the rapid pace of social change.Methods. To achieve the goal, the article raises 3 research questions, which are answered by combining the review of contemporary literature, the quantitative and qualitative methods, and by combining primary and secondary data, obtained from the analysis of the questionnaires, and the comparison with the positive examples in the region and beyond. The questionnaires distributed electronically were completed by pupils and teachers of 161 schools in 4 Regional Directorates of Pre-University Education.Results. Results emphasise that the inclusion of these skills has the great potential to significantly improve the better preparation of pupils for the labour market and to contribute to the improvement of quality education in Albania.Conclusion. In the end, the article highlights the importance of this integration in building a more united and stronger society for the future.